Public Health and Health Sector Crisis Leadership During Pandemics: A Review of the Medical and Business Literature. (August 2022) - Sriharan, Abi; Hertelendy, Attila J.; Banaszak-Holl, Jane; Fleig-Palmer, Michelle M.; Mitchell, Cheryl; Nigam, Amit; Gutberg, Jennifer; Rapp, Devin J.; Singer, Sara J.
The global scale and unpredictable nature of the current COVID-19 pandemic have put a significant burden on health care and public health leaders, for whom preparedness plans and evidence-based guidelines have proven insufficient to guide actions. This article presents a review of empirical articles on the topics of "crisis leadership" and "pandemic" across medical and business databases between 2003 (since SARS) and—December 2020 and has identified 35 articles for detailed analyses. We use the articles' evidence on leadership behaviors and skills that have been key to pandemic responses to characterize the types of leadership competencies commonly exhibited in a pandemic context. Task-oriented competencies, including preparing and planning, establishing collaborations, and conducting crisis communication, received the most attention. However, people-oriented and adaptive-oriented competencies were as fundamental in overcoming the structural, political, and cultural contexts unique to pandemics.